A MALDI-TOF MS library for rapid identification of human commensal gut bacteria from the class Clostridia - Asare, Paul Tetteh; Lee, Chi-Hsien; Hürlimann, Vera; Teo, Youzheng; Cuénod, Aline; Akduman, Nermin; Gekeler, Cordula; Afrizal, Afrizal; Corthesy, Myriam; Kohout, Claire; Thomas, Vincent; de Wouters, Tomas; et al. (Frontiers in Microbiology, 2023)
Microbial isolates from culture can be identified using 16S or whole genome sequencing which generates substantial costs and requires time and expertise. Protein fingerprinting via Matrix associated Laser Desorption Ionization – time of flight mass spectrometry (MALDI-TOF MS) is widely used for rapid bacterial identification in routine diagnostics but shows a poor performance and resolution due to currently limited database entries capturing only few commensal gut bacteria. The aim of this study was to develop a MALDI-TOF MS plugin database (CLOSTRI-TOF) allowing for rapid identification of non-pathogenic human gastrointestinal bacteria. We constructed a database containing mass spectral profiles (MSP) from 142 bacterial strains representing 47 species and 21 genera within the class Clostridia. Each strain-specific MSP was constructed using >20 raw spectra measured on a microflex system (Bruker-Daltonics) from two independent cultures. During the validation part, we used 58 sequence-confirmed strains and the CLOSTRI-TOF database successfully identified 98% and 93% of the strains, respectively, in two independent laboratories. Next, we applied the database to 326 isolates from stool of healthy Swiss volunteers and identified 264 (82%) of all isolates (compared to 170 (52.1%) with the Bruker-Daltonics library alone), thus classifying 61% of the formerly unknown isolates. We describe a new opensource MSP database for fast and accurate identification of the Clostridia class from the human gut microbiota. CLOSTRI-TOF expands the number of species which can be rapidly identified by MALDI-TOF MS.